The Relationship Between Educational Level of Fertile Age Women and Contraception Knowledge to Prevent the Unwanted Pregnancy in the COVID-19 Pandemic Era - Annita Viesta Nirmala Dewi; Nudiya Salwa Syifa Kamila; Siti Nurhidayati (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2021)
Indonesia has the potential for a baby boom after the COVID-19 pandemic. The cause of this issue is the decline of contraception used by fertile age couples. The decline of contraception used lead to unwanted pregnancies. This study were conducted to find out the relationship about educational level in fertile age women regarding contraception. This cross-sectional study was done in 27 provinces in Indonesia and it was found about 279 fertile age women with different educational backgrounds. The respondents who met the inclusion criteria were married women by 104 people from 19 different provinces. The educational level groupings are intermediate (Middle School and High School), vocational (D1/D2/D3), and higher education (Bachelor/Master). The respondents were asked to answer questions about contraceptives through questionnaires distributed on social media. Next, the data were process by using univariate dan bivariate as well as the chi square test with 24 version of SPSS. The result showed that 53.8% of respondents who have good knowledge about contraception, respondents who have poor knowledge about contraceptives are 46.2%. There is a relationship between educational level of fertile age women and knowledge about contraception (p-value: 0,001), and the unmet need is one of the factors which causes unwanted pregnancies, therefore, the efforts are needed to eliminate unmet need to reduce the incidence of unwanted pregnancies during the COVID-19 pandemic.